2011
DOI: 10.1002/er.1832
|View full text |Cite
|
Sign up to set email alerts
|

Anode-supported solid oxide fuel cells with ion conductor infiltration

Abstract: SUMMARYNano ion conductor infiltration to anode andcathode side of solid oxide fuel cell (SOFC) significantly improves the performance of an SOFC. The effects of processing parameters such as molar concentration, sintering temperature and holding time are investigated. The performance of fuel cell is evaluated with a test station and an impedance analyzer. The SEM investigation showed that a nano ion conductor phase forms around the main phase in the anode and the cathode. The results showed that nano infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…This can be achieved by the anode supported cell configuration with thin electrolyte layer of around 10 mm [19,20] or employing alternative electrolyte materials. Several papers have reported very good performance for nickel oxide (NiO)/YSZ anode supported SOFCs.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by the anode supported cell configuration with thin electrolyte layer of around 10 mm [19,20] or employing alternative electrolyte materials. Several papers have reported very good performance for nickel oxide (NiO)/YSZ anode supported SOFCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult for commercial SOFC materials to weigh the gains and losses when both stable power output and low cost are needed . The exciting discovery is that surface modification through metal salt solution infiltration/impregnation provides an effective way of developing highly active and durable structures for SOFCs …”
Section: Introductionmentioning
confidence: 99%
“…4 The exciting discovery is that surface modification through metal salt solution infiltration/impregnation provides an effective way of developing highly active and durable structures for SOFCs. 5 According to the reported literature, 6,7 the architecture of infiltrated electrodes involves 3 main categories, that is, (1) single-phase nanoparticle infiltrated singlephase backbone, (2) dual/multiphase nanoparticle infiltrated single-phase backbone, and (3) single/multiphase nanoparticle infiltrated dual/multiphase backbone. The first type of infiltrated electrodes is the most usually reported, showing remarkably lower polarization resistance as compared with the composite electrodes fabricated by high-temperature sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Loadings of 0.96 mmol cm -3 (two infiltration cycles) and 1.41 mmol cm -3 (three sequential infiltration cycles) led to an increase of the maximum power output by 8 and 22%, respectively. Timurkutluk et al [12] infiltrated gadolinium doped ceria (CGO) precursor ink into the anode and cathode of NiO-ScSZ/ScSZ/LSF-ScSZ button cells. After five infiltration passes it was found that at 700°C the cell impregnated with 1.5 M solution provides peak power density of 1.34 W cm -2 compared to the cell without impregnation producing only 0.78 W cm -2 .…”
Section: Introductionmentioning
confidence: 99%